Land-use and ceramics in the Andean highlands of Patagonia, Argentina - Franchetti, Fernando Ricardo (2024)
The aim of this paper is to study the use of ceramics of small-scale societies during the late Holocene in northern Patagonia. The technological investment model predicts that use-time and utility will determine the investment spent in ceramics. We explore how ceramics were used in short-term camps and aggregation sites during summer at high elevations, and residential camps during winter at lower elevations. To test the investment in ceramics we use fourtechnological variables: temper size, average thickness, surface treatment and firing. Our results indicate that hunter-gatherers expected a short-term use in summer locations and therefore made a low investment in ceramics.